Heating Coil Pipe Stress Analysis of Thermal Oil Plant on Fuel Oil Tanks of 17500 LTDW Product Oil Tanker - Juda Imanuel Osvaldo Panggabean; Taufik Fajar Nugroho; Wolfgang Busse (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2017)
The heating coil pipe is one of the most important equipment in the thermal oil system. The pipe is located within each of the fuel tanks, which will be used as a place for thermal oil fluid flow in order to transfer heat to the fuel inside the tank. The equipment has been installed on 17500 LTDW Product Oil Tanker, MT. Parigi, but not yet tested. Meanwhile, the system will be operated at working pressure of 5 kgf/cm2 and working temperature of 180oC. Therefore, it is needed an evaluation or analysis to ascertain whether the equipment is capable of or not withstand the working pressure and working temperature of the system, namely pipe stress analysis. This analysis was performed by using the simulation of a software, namely Caesar II with ASME B31.3 as the code standard. The result concludes that the heating coil pipes inside each fuel tank are safe to operate, which means that the allowable stress of the pipe is bigger than the stress result value.